Training in Mathematics in Colombia: a view from a standpoint of gender - González-Gutiérrez, Nelsy Rocío; Sepúlveda-Delgado, Omaida; Espejo-Lozano, Ruby Lisbeth (Universidad Pedagógica y Tecnológica de Colombia, 2018)
This research shows an overview of what has been the scientific training of women in Colombia. For this purpose, and as a particular case, here are some theoretical references used to carry out the study of the history of mathematics in the Colombian universities from a gender perspective. This research was oriented to determine what participation Colombian scientist women have had in terms of contributions, access, development and permanence in the investigative processes of areas predominantly occupied by men, such as Mathematics. This led to analyze how the work developed by these scientist women has contributed to the existing educational processes. The model to analyze the object of study: women in Mathematics in Colombia was the historiographic current of social history in education. The analysis carried out offers indications that contribute to the disarticulation of certain gender stereotypes existing in the conception of science, seeking to provide some strategies that allow the process of women's empowerment in the face of sciences to be improved.